Lecturers’ Assertive Speech Acts in Teaching English - Nilma Taula’bi’ (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This research objectives is to find out the lecturers’ assertive speech acts in teaching English. The method used in this research is qualitative research method. The participant are the lecturers in English Eduation Study program of FKIP UKI Toraja. The instruments used to collect the data are interview and observation. The data analyzes by Miles and Huberman theory. The lecturers’ assertive speech acts in teaching English at English Education Study Program of FKIP UKI Toraja are are (1) Assetive used to explaining the material, evaluating the students, opening the class, and concluding the lesson. It is expressed directly and indirectly which function as statement and command. (2) Affirmative used to explaining the material, asking about the term, giving example, concluding the lesson and sharing experience. The utterances expressed directly and indirectly which functions as statement, question, command, and request. The syntactic forms are declarative and interrogative. (3) Informative used by the lecturer to explain the material in teaching and learning process. The utterance categorized as direct speech act which functions as statement.